MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI MEDIA BAHAN ALAM PADA ANAK USIA 4-5 TAHUN DI TK AL RASYID PEKANBARU - Irmawati '; Tri Umari; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Research using batik activities conducted in TK Al Rashid Pekanbaru city. The study lasted for 2 months and consists of 2 cycles. In conducting the study, researchers helped by colleagues elected observer in kindergarten Al Rashid. That is the subject of this study is that children in group A were 18 children ranging from 7 boys - men and 11 daughters. Class Action Research was conducted from April to May 2016. The average value of 51.5 in the first cycle, it can be said that the fine motor skills of children in the position of the new criteria or start to grow, so it is necessary to continue to the next cycle (Cycle II ). In the second cycle of fine motor skills of children through making polosa got an average rating of 67.5 with both criteria. Thus, the increase of the first cycle to the second cycle of 31.1%, while the increase in the amount of the fine motor skills of children before the cycle to the second cycle was 83.9%. From these data suggest that the activity of weaving can improve fine motor skills of children aged 4-5 years in kindergarten Rashid Al Pekanbaru